Reinforcement learning in motor skill acquisition: using the reward positivity to understand the mechanisms underlying short- and long-term behavior adaptation - Bacelar, Mariane F. B.; Lohse, Keith R.; Parma, Juliana O.; Miller, Matthew W. (Frontiers in Behavioral Neuroscience, 2024)
Introduction According to reinforcement learning, humans adjust their behavior based on the difference between actual and anticipated outcomes (i.e., prediction error) with the main goal of maximizing rewards through their actions. Despite offering a strong theoretical framework to understand how we acquire motor skills, very few studies have investigated reinforcement learning predictions and its underlying mechanisms in motor skill acquisition. Methods In the present study, we explored a 134-person dataset consisting of learners’ feedback-evoked brain activity (reward positivity; RewP) and motor accuracy during the practice phase and delayed retention test to investigate whether these variables interacted according to reinforcement learning predictions. Results Results showed a non-linear relationship between RewP and trial accuracy, which was moderated by the learners’ performance level. Specifically, high-performing learners were more sensitive to violations in reward expectations compared to low-performing learners, likely because they developed a stronger representation of the skill and were able to rely on more stable outcome predictions. Furthermore, contrary to our prediction, the average RewP during acquisition did not predict performance on the delayed retention test. Discussion Together, these findings support the use of reinforcement learning models to understand short-term behavior adaptation and highlight the complexity of the motor skill consolidation process, which would benefit from a multi-mechanistic approach to further our understanding of this phenomenon.